ON SUCCESSION IN THE NOMOCANON OF SAINT SAVA - Stojanovic, Natasa (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
The author’s attention is focused on the rules establishing the institution of succession in the Nomocanon of Saint Sava. Through a prism of provisions dedicated to legal, testamentary and forced succession, the author sheds light to the characteristics in regulating inheritance-law relationships in the medieval Serbia, particularly focusing her attention to the degree of applicability of individual solutions in practice. The author advocates for the return to roots, reaffirmation, and for a comprehensive study of almost completely forgotten civil society rules contained in the Nomocanon of Saint Sava.